Report Of The Working Group on Organic and Biodynamic Farming for The Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, 2001)
Although, as yet infancy, Organic Farming is becoming important in the agriculture sector in India, largely through the efforts of small groups of farmers. It has come out of the exploitative agriculture that has been followed by in all these years, resulting into damaging impacts on environment, human and animal health, soil and water resources. It is well known now that increased use of chemical pesticides (rather abuse) and fertilisers have created chain of problems of soil, environment and water degradation. The intensive chemical agriculture that has been followed after green revolution successes is causing heavy pollution of our food, drinking water, air, the life expectancy has improved, but the quality of life has substantially deteriorated. The rural economy is in ruins because of over-dependence of Outside inputs in agriculture such as seed, fertilisers.
Government of India Planning Commission
Government of India Planning Commission